2016
DOI: 10.4028/www.scientific.net/kem.712.195
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of «TiC-HSS Steel Binder» Composite Powders by Self-Propagating High Temperature Synthesis

Abstract: The phase composition, microstructure and morphology of composite powders «TiC-HSS steel binder» obtained by the SHS method in layerwise combustion mode have been studied. Titanium powder, carbon (carbon black) in a ratio corresponding to equiatomic titanium carbide and high speed steel as a thermally inert binder was used as a reaction mixture. It was found that the mass transfer of reaction mixture components between the carbide and metal binder was taking place during synthesis, as a result of which the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It was found that the non-equilibrium metal-matrix structure of the powders formed as a result of SHS by the layerwise combustion method consisting mainly of non-stoichiometric titanium carbide [30,31]. Many works are devoted to the non-stoichiometricity of titanium carbide [6,[8][9][10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the non-equilibrium metal-matrix structure of the powders formed as a result of SHS by the layerwise combustion method consisting mainly of non-stoichiometric titanium carbide [30,31]. Many works are devoted to the non-stoichiometricity of titanium carbide [6,[8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…The combustion product remains of titanium silicide were removed after synthesis; the reacted compact was milled and sieved into fractions. Using this procedure, synthesized powders of all investigated compositions containing titanium carbide were obtained [28][29][30][31][32]. The typical microstructure and morphology of the studied synthesized powder compositions are shown in Figure 1.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation